(untitled) (Fiep Bulletin - online, 2011)
The objective of this study is to analyze the body composition obtained by the methods of skin folds and circumference of schoolchildren in the Federal Institute of Education, Science and Technology, campus Juazeiro do Norte, CE, Brazil. Derive from a side study in a sample of 79 characters (37 males and 42 females), mean age 16.0 + 1.1 years, coming from the Federal Institute of Education, Science and Technology (IFCE), campus Juazeiro do Norte, Ceará, they were submitted to measuring of body composition by skin folds of triceps, sub scapular, to obtained the percentage of fat (% BF) by the equation of Slaughter (1988) and measure too, the perimeter of the proximal thigh(cm) and body mass(kg) to perform the calculation of estimates for %BF from the prediction of lean body mass (LBM) developed by Yonamine (SOUSA, 2008). The data analysis plan derives from a statistics program by the descriptive and conclusive with the t test of Student to independent samples and level of significance equal to 5%. The results had presented: average e sd equal to 47,2+8,6 and 42,6+7,14 to the LBM of a perimeter and folds, average and sd equal to 15,7+3,4 and 23,3+9,6 to the %BF of perimeter and folds respectively, after the conclusive test was done, a significant difference was shown p=(0,001) between males and females to the perimeter of LBM and to the folds and to the %BF too; the r correlation test of Pearson had pointed a low and positive correlation (r=0,573) for %BF, and at LBM, the presented values are high (r=0.726). Conclusions: The evaluate method by skin folds, to the fat percentage seems to be more reliable than the perimeter one, while the perimeter one, shows to be more tendency to the LBM, in adolescents students.